2019
DOI: 10.1111/evj.13183
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory mediators are potential biomarkers for extracorporeal shockwave therapy in horses

Abstract: Summary Background Extracorporeal shockwave therapy (ESWT) can potentially mask painful injuries in equine athletes. Tests to detect whether a horse has received ESWT prior to competition are needed. Extracorporeal shockwave therapy is known to affect inflammatory mediators in other species, and if these mediators are altered in the horse, these could serve as biomarkers of ESWT. Objectives To test the hypothesis that a single application of ESWT will alter the circulating protein concentrations of 10 inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…IL-1Ra protein was also increased in the corresponding plasma samples. 16 Importantly, this study demonstrates an increase in the gene transcript for IL1β in circulating WBC, while the study of the corresponding plasma samples from the same administration study found a decrease in IL1β protein expression. 16 This is not an unusual finding; studies of gene transcription and protein expression for the same target often find differing effects of a treatment or condition on the gene transcript and protein expression levels.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…IL-1Ra protein was also increased in the corresponding plasma samples. 16 Importantly, this study demonstrates an increase in the gene transcript for IL1β in circulating WBC, while the study of the corresponding plasma samples from the same administration study found a decrease in IL1β protein expression. 16 This is not an unusual finding; studies of gene transcription and protein expression for the same target often find differing effects of a treatment or condition on the gene transcript and protein expression levels.…”
Section: Discussionmentioning
confidence: 57%
“…16 Importantly, this study demonstrates an increase in the gene transcript for IL1β in circulating WBC, while the study of the corresponding plasma samples from the same administration study found a decrease in IL1β protein expression. 16 This is not an unusual finding; studies of gene transcription and protein expression for the same target often find differing effects of a treatment or condition on the gene transcript and protein expression levels. The regulation of protein translation from the gene transcripts is a complex process with a number of regulatory steps, underscoring the importance of assessing each type of potential biomarker directly.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations